Teaching Reading Comprehension on Narrative Texts Through Whatsapp Group Features: An E-Learning Implementation in Junior Highs Schools - Aniati, Aniati; Herman, Herman; Siregar, Christina Anita Elizabeth; Afrianti, Desi; Manurung, Rolan; Fatmawati, Endang; Saputra, Nanda (Journal of Languages and Language Teaching, 2025)
The act of reading necessitates that student readers employ various cognitive and linguistic tactics to comprehend the meaning embedded within the text. Using an e-learning method through WhatsApp groups to teach reading comprehension on narrative texts can be a new breakthrough. Therefore, the present study aims to find out the effect of WhatsApp groups on narrative text in junior high school students to teach reading comprehension. To reach the research aims, the study used experimental research method. The population of this research was 330 students of grade 9 of junior high school in Pematangsiantar. The researchers divided the samples intor control group and experimental group. The data collection method used was the reading tests employed to the students which covered pre-test, treatment, and post-test. The statistical analysis employed t-test analysis. Comparison of data from both groups indicated superior performance by the experimental group. The findings unequivocally show that the experimental intervention employing WhatsApp have significant effect on students’ reading comprehension of narrative text compared to traditional approaches. While WhatsApp has proven to be an effective tool, researchers must consider the challenges of using it for reading instruction in remote areas with limited internet connectivity. Students cannot access WhatsApp-based reading lessons without internet access, though they can still search for information through text messages. Therefore, it is important to examine the limitations of utilizing WhatsApp for reading education in areas with poor internet infrastructure.